Reducing Conditions Favor Magnetosome Production in Magnetospirillum magneticum AMB-1 - Olszewska-Widdrat, Agata (Front Microbiol, 2019)
Magnetotactic bacteria (MTB) are a heterogeneous group of Gram-negative prokaryotes, which all produce special magnetic organelles called magnetosomes. The magnetosome consists of a magnetic nanoparticle, either magnetite (Fe(3)O(4)) or greigite (Fe(3)S(4)), embedded in a membrane, which renders the systems colloidaly stable, a desirable property for biotechnological applications. Although these bacteria are able to regulate the formation of magnetosomes through a biologically-controlled mechanism, the environment in general and the physico–chemical conditions surrounding the cells in particular also influence biomineralization. This work thus aims at understanding how such external conditions, in particular the extracellular oxidation reduction potential, influence magnetite formation in the strain Magnetospirillum magneticum AMB-1. Controlled cultivation of the microorganisms was performed at different redox potential in a bioreactor and the formation of magnetosomes was assessed by microscopic and spectroscopic techniques. Our results show that the formation of magnetosomes is inhibited at the highest potential tested (0 mV), whereas biomineralization is facilitated under reduced conditions (-500 mV). This result improves the understanding of the biomineralization process in MTB and provides useful information in sight of a large scale production of magnetosomes for different applications.